Fifty Years of Collecting: The Sale of Ancient Maya Antiquities at Sotheby's. Issue 2 (23rd June 2017) - Tremain, Cara Grace
Abstract: Pre-Columbian antiquities, particularly those from the Maya region, are highly sought after on the international art market. Large auction houses such as Sotheby's have dedicated pre-Columbian departments and annual auctions, for which sales catalogues are created. These catalogues offer insight into market trends and allow the volume of antiquities being bought and sold to be monitored. The following study records the public sale of Maya antiquities at Sotheby's over a period slightly exceeding 50 years from 1963 to 2016. More than 3, 500 artifacts were offered for sale during this period, of which more than 80 percent did not have associated provenance information. The data suggests that the volume of Maya antiquities offered for sale at Sotheby's public auctions have been steadily decreasing since the 1980s, but their relative value has increased. Quantitative studies of auction sales such as this one can be useful in monitoring the market for illegal antiquities and forgeries.